Data Security and Policy Management in E-Government Cloud Platforms: A Systematic Review of Challenges and Opportunities in Archipelagic Nations - Hasan, Mochammad Fuad (International Journal of Research and Applied Technology (INJURATECH), 2024)
The adoption of cloud computing in e-government offers significant scalability but presents unique architectural and regulatory complexities for archipelagic nations due to geographical fragmentation. This systematic literature review investigates the intersection of cloud data security, policy management, and topographical constraints. Following the PRISMA protocol, we analyzed 42 peer-reviewed articles (2019–2026) from Scopus, IEEE Xplore, and ScienceDirect. The findings reveal a critical "archipelagic latency trap," physical infrastructure vulnerabilities at edge nodes, and significant ambiguities in distributed data sovereignty across local autonomous jurisdictions. Existing centralized security frameworks are proven inadequate for these decentralized topologies. Consequently, we propose the necessity of an Archipelagic Cloud Governance Framework integrating Hybrid Edge-Cloud architectures and Consortium Blockchain technologies. This approach mitigates inter-island synchronization failures while ensuring immutable audit trails and regulatory compliance. Ultimately, this study provides a foundational roadmap for policymakers engineering resilient, geographically-adapted public service infrastructures.